Motoric Potential of Freshmen in Physical Education, Sports and Health Study Program (PJOK) Faculty of Sports and Health Universitas Negeri Gorontalo Class of 2022 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2023)
Motoric potential must be owned by every new student, especially those who concentrate on the Physical Education, Sports and Health (PJOK) study program. It is important because most of the lectures in the PJOK study program are field-based courses. The purpose of this study was to determine the motor potential of freshmen of the PJOK study program, Faculty of Sports and Health (FOK), Universitas Negeri Gorontalo (UNG) class of 2022 who successfully passed the college entrance through the portfolio program. The research method used in this research was descriptive method. The research population was all new students of the 2022 PJOK FOK UNG study program, totalling 77 people, including 63 male students dan 14 female students. The form of the test used in this study referred to the pattern of motor tests in general, namely throwing and catching tennis balls, push-ups, sit-ups, agility and vertical jumps and bleep tests. The results showed that the freshmen of PJOK FOK UNG class of 2022 were divided into 2 groups: first, the male group had motor skills by category; very good (11 students or 17.45%), good (20 students or 31.74%), moderate (23 students or 36.50%) and poor (6 students or 9.52%) and very poor (3 students or 4.76%). Second; the group of women with very good and good categories did not exist or 0%, while there were 7 students (50%) in the moderate category, and 3 students (21.42%) in the poor category, and 4 students (28.57%) in the very poor category. It can be concluded that the motor potential of freshmen of PJOK study program, faculty of sports and health class of 2022 at the UNG needs serious attention